A Simulated Kalman Filter (SKF) approach in identifying optimum speed during cornering - Kamil Zakwan, Mohd Azmi; Nurul Afiqah, Zainal; Muhammad Aizzat, Zakaria; Anwar, P. P. Abdul Majeed (Springer, Singapore, 2021)
Safety and human comfort are of paramount importance towards vehicle performance. This study aims to recognize the optimum cornering speed of a two-in wheel vehicle by means of a metaheuristic optimization technique known as Simulated Kalman Filter (SKF). The algorithm is used to minimize the normal forces experienced by the driver based on the identified speed. The system combines a biodynamic model with a two-in-wheel car model. It was demonstrated from the study that the conservative optimum speed of 20 km/h was determined by the SKF algorithm. The outcome of the investigation is non-trivial towards ensuring human comfort as well as safety to the driver.